Lviv National Medical University Scientific Library – a history of the library (Journal of EAHIL, 2016)
The history of the library began in 1939 when the Medical Faculty was separated from Lviv University and became the Lviv State Medical University. The history of the library is closely connected with the name of Stanislav Henry Badeni in whose house it is still situated. Today the library is being transformed from a subunit of the University which provides students and scientists with the necessary literature into a powerful research and information center